Design of an integrated membrane bioreactor process for effective and environmentally safe treatment of highly complex coffee industrial effluent. (October 2020) - Chandrasekhar, Sajja S.; Vaishnavi, D.; Sahu, Nivedita; Sridhar, Sundergopal
Graphical abstract: Abstract: Food and beverage industries produce huge quantities of wastewater every day, with the coffee industry being one of the largest producers of effluents that pose grave environmental challenges due to high organic loading rate, strong odor and color. In the present study, the authors have investigated the performance of an integrated membrane bioreactor (IMBR) system using a combination of a biological process with side-steam ultrafiltration (UF) and subsequently reverse osmosis (RO) for the treatment of coffee industrial effluent. A significant reduction in chemical oxygen demand (COD) from 20, 000 to 40 mg/L and turbidity from 1100 formazin attenuation unit (FAU) to 0 FAU, was achieved along with a considerable reduction in conductivity by 94 % (1.5 to 0.09 mS/cm) and total dissolved solids (TDS) by 76 %. The results revealed significant potential for meeting the acceptable range of parameters for safe disposal as specified by the central pollution control board (CPCB), while the recovered water was of a quality suitable enough for industrial reuse. A scale-up ratio of 10 from 2 L to 20 L in effluent batch size showed reproducible performance with pollutant diminution getting accelerated after 15 days to exhibit a significant removal of all pollutants, which emphasizes the effectiveness of the IMBR technology in meeting the environmental safety norms. This study reports for the first time 100 % separation of turbidity, color, and odor along with 99 % COD removal while successfully processing coffee industrial effluent. An economic estimate of a 1000 L/h capacity system confirms the commercial viability of the (IMBR) configuration.